Ets oncogene-related gene Elg functions in Drosophila oogenesis. - Schulz, R.A.; The, S.M.; Hogue, D.A.; Galewsky, S.; Guo, Q. (Proceedings of the National Academy of Sciences of the United States of America, 1993)
Members of the ets gene family encode transcription factors that regulate the expression of a variety of cellular and viral genes including several protooncogenes. We have utilized Drosophila to elucidate the in vivo function of one family member. We show by complementation rescue and sequence analysis that the female sterile mutant tiny eggs (tne) is an allele of the Drosophila Ets-related gene Elg (also called D-elg). The mutation of a highly conserved tyrosine residue in the ETS DNA-binding domain of the Elg gene product demonstrates that normal gene function is required for proper follicle cell migration, chorion formation, and nurse cell-chromosome decondensation during Drosophila oogenesis.